Gyoji Banshoya (1930-1998): a Japanese planner devoted to historic cities in the Middle East and North Africa - Matsubara, Kosuke (Planning perspectives, 2016)
Gyoji Banshoya (1930-1998) was a Japanese urban planner whose life-work was urban planning in the Middle East and North Africa. The purpose of this paper is to provide an overview of his work, which still remains unknown. His early masterpiece, the 'Square House', shows how he was influenced by Kiyoshi Seike to apply historic spatial composition to realize width and convertibility in low-cost housing. Following this, Banshoya studied under the supervision of Gerald Hanning and George Candilis at Ateliers de Bâtisseurs in Paris, and went to Algiers to engage in the study of 'evolutionary habitat'. As a United Nations Development Programme (UNDP) expert, he began working with Michel Ecochard in 1962 in Beirut, Damascus, and Aleppo. They were responsible for the elaboration of master plans for these three cities, and that of Damascus still remains as a legally active master plan today. Coupled with the Syrian political struggle since the 1980s, there has been some reaction against their modernist policies. However, the case is made for a detailed examination of Banshoya's work, and re-evaluation of its legacy for the urban planning history of the Middle East and North Africa.